2017
DOI: 10.1177/0194599817721154
|View full text |Cite|
|
Sign up to set email alerts
|

Unplanned 30‐Day Readmissions after Parathyroidectomy in Patients with Chronic Kidney Disease: A Nationwide Analysis

Abstract: Objective To examine rates of readmission after parathyroidectomy in chronic kidney disease patients and determine primary etiologies, timing, and risk factors for these unplanned readmissions. Study Design Retrospective cohort study Setting Nationwide Readmissions Database Subjects and Methods The Nationwide Readmissions Database was queried for parathyroidectomy procedures performed in chronic kidney disease patients between 1/2013 - 11/2013. Patient, admission, and hospital-level characteristics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…e most frequent indication is primary HPT (59.89%) by secretory adenoma, described in the general population, with some cases isolated in ERSD, the second indication of PTX is secondary HPT (21.9%), which is present in ERSD [7]. e PTX outcomes in dialysis patients are worse than in patients without CKD, and there is a higher probability of adverse events due to comorbidity: diabetes mellitus, hypertension, and heart failure [14]. Hospital readmissions and postparathyroidectomy mortality are 5 times more frequent than in the general population, with the subsequent impact on costs for health systems [7,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e most frequent indication is primary HPT (59.89%) by secretory adenoma, described in the general population, with some cases isolated in ERSD, the second indication of PTX is secondary HPT (21.9%), which is present in ERSD [7]. e PTX outcomes in dialysis patients are worse than in patients without CKD, and there is a higher probability of adverse events due to comorbidity: diabetes mellitus, hypertension, and heart failure [14]. Hospital readmissions and postparathyroidectomy mortality are 5 times more frequent than in the general population, with the subsequent impact on costs for health systems [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…e PTX outcomes in dialysis patients are worse than in patients without CKD, and there is a higher probability of adverse events due to comorbidity: diabetes mellitus, hypertension, and heart failure [14]. Hospital readmissions and postparathyroidectomy mortality are 5 times more frequent than in the general population, with the subsequent impact on costs for health systems [7,14]. Kuo et al studied 898 dialysis patients and found 30-day readmission rates of 17.8%, [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2756 parathyroidectomy procedures were performed in patients with CKD, with unplanned readmission rate of 17.2 and 6.8% due to hypocalcemia/ hungry bone syndrome. In one study, readmission occurred within 30 days after discharge, but readmission for severe hypocalcemia peaked within just 10 days and decreased thereafter [32].…”
Section: Readmission Ratementioning
confidence: 98%
“…It has been seen in the literature that the number of cases with parathyroidectomy due to secondary hyperparathyroidism in children and adolescents is low, and it is mostly performed by adult surgeons [12][13]. The experience of adult surgeons does not fully reflect the treatment and follow-up methods related to children.…”
Section: Introductionmentioning
confidence: 99%